2014
DOI: 10.1021/jp408859s
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Chiral Resolution: Methyl 2-Ammonium Chloride Propanoate on Al(854)SSurface

Abstract: The adsorption of the chiral methyl 2-ammonium chloride propanoate ionic liquid on the chiral Al(854) S surface has been investigated by density functional calculations on periodic slab models. The results show that the molecule features an enantioselective dissociative adsorption at the surface chiral center. The low-coordination of Al atoms at kinked steps and the strong attractive forces towards molecular O atoms are the main causes of the dissociation. At the surface, 2-ammonium propanal, methoxy groups, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…The strong interaction between ions and metals may provide a route to separating enantiomers of chiral ILs . This was elegantly demonstrated by Jalili et al who showed enantiospecific chemisorption of ( R )- and ( S )-methyl 2-ammonium chloride propanoate on achiral Al(111) and on chiral Al(854) S surfaces via ab initio calculations. It would be interesting to test the broader applicability of this result, that is, whether it could be used to separate mixtures of chiral ions or chiral ILs dissolved in molecular solvents by exploiting the pronounced structuring of ILs at interfaces.…”
Section: The Structure Of the Solid–ionic Liquid Interfacementioning
confidence: 93%
“…The strong interaction between ions and metals may provide a route to separating enantiomers of chiral ILs . This was elegantly demonstrated by Jalili et al who showed enantiospecific chemisorption of ( R )- and ( S )-methyl 2-ammonium chloride propanoate on achiral Al(111) and on chiral Al(854) S surfaces via ab initio calculations. It would be interesting to test the broader applicability of this result, that is, whether it could be used to separate mixtures of chiral ions or chiral ILs dissolved in molecular solvents by exploiting the pronounced structuring of ILs at interfaces.…”
Section: The Structure Of the Solid–ionic Liquid Interfacementioning
confidence: 93%
“…Many commercial drugs in current use contain chiral structures and thus consist of enantiomers. The biological effects of enantiomers such as toxicity, mutagenicity, carcinogencity, and endocrine disruption activity are generally different [2][3][4][5][6][7]. Therefore, resolution of chiral herbicides has attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%